Sorotan pers tentang ketenagakerjaan 1988-1993 : pewawancara penulis Ponco ES Pratiknyo ... [et al.] ; penyunting Yatim zkelana ... [et al.] - Pratiknyo, Ponco ES (PWI Jaya, 1993)
ix, 406 p. : il.; 21 cm.